Prostate cancer – peculiarities of the process of adaptation to the disease - Grigorean, Valentin Titus; Nita, Gabriela Rahnea; Nita, Roxana Ancreea Rahnea; Popescu, Mihai; Sandu, Aurelia Mihaela; Lupascu, Cristian Dumitru (Medicine and Pharmacy Reports, 2013)
Aim. Psycho-social adaptation to the diagnosis of cancer is a dynamic process, different from one patient to another, depending on many factors (location, stage, treatment, personality of each individual, environment - family, professional background, social-economic-cultural status). The aim of this study is to analyze the process of adaptation of patients with prostate cancer. Patients and method. Thirty six patients diagnosed with prostate cancer, admitted in the Department of Oncology, Palliative Care for Chronic Patients within Chronic Disease Hospital “St. Luke” from Bucharest, Romania, over a period of six months, answered the Illness Cognition Questionnaire (ICQ), in order to assess adaptation to the disease (helplessness, acceptance, perceived benefits). Results. Results of the study showed that feelings of helplessness were expressed at a high level in 22.2% patients, medium level in 55.6% cases and low level 22.2%. The feelings of acceptance were the following: 61.1% of patients had a high level, 33.3% of them a medium level, while only 5.6% had a low level of acceptance. Regarding perceived benefits due to the disease, the following results have been obtained: 22.2% had a high level, 77.8% a medium level and no patient reported low level benefit. Conclusion. The results of this study indicate that patients diagnosed with prostate cancer adapt well to the disease, accept it and even obtain benefits from it.